Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Guru di Madrasah Tsanawiyah Negeri 1 Sukoharjo The Influence of Leadership Style, Work Motivation and Work Discipline on Teacher Performance at Madrasah Tsanawiyah Negeri 1 Suk - Priyantika, Devila Irlan; Handayani, Asih (EBBANK, 2025)
Both the business world and institutional institutions are highly dependent on human resources. This study aims to determine the effect of leadership style, work motivation, and work discipline on teacher performance at MTs Negeri 1 Sukoharjo. All ASN teachers at MTs Negeri 1 Sukoharjo are the population in this study, with a sample consisting of all existing ASN teachers. Data collection was carried out through a quantitative approach using a questionnaire. Data analysis includes descriptive analysis, statistical tests, multiple linear regression, and determination coefficient tests. The results of the study indicate that leadership style has a positive and significant effect on teacher performance. Likewise, work motivation plays a role in significantly improving teacher performance. In addition, work discipline has also been shown to have a positive impact on teacher performance. Thus, it can be concluded that leadership style, work motivation, and work discipline as a whole contribute to improving teacher performance at MTs Negeri 1 Sukoharjo.